(untitled) (Altre Modernità, 2017)
Nicoletta Vallorani (a cura di), Introduzione ai Cultural Studies (Roma, Carocci, 2016, pp. 209, ISBN 978-88-430-8480-7) Floriana Bernardi (ed.), Italian Cultural Studies (Cardiff, JOMEC Journal 8, Cardiff University Press, 2015, ISSN 2049-2340 )